2002
DOI: 10.1590/s0100-204x2002000700012
|View full text |Cite
|
Sign up to set email alerts
|

Freqüência de híbridos em cruzamentos controlados de citros: cultivo de sementes versus cultivo in vitro de embriões

Abstract: Os objetivos deste trabalho foram estudar a freqüência de híbridos oriundos de cruzamentos controlados em citros, comparando a germinação de sementes em canteiros com o cultivo in vitro de embriões, e analisar o efeito da remoção dos tegumentos da semente na germinação. Como parentais femininos foram utilizadas as tangerineiras 'Clementina Palazelli' e 'Sunki', os limoeiros 'Cravo Santa Bárbara' e 'Volkameriano Catânia 2' e as laranjeiras Azedas 'Comum' e 'Double Calice'. Os parentais masculinos compreenderam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
0
1
1
Order By: Relevance
“…Germination evaluation of intergeneric hybrids between Citrus and Poncirus indicated that coated seeds led to a longer germination period and seed coat removal did not influence germination rate [6]. However, in our work, 60 days after sowing, plant emergence was higher for Rangpur lime coated seeds (75%) than for Rangpur lime decoated seeds (15%) (figure 2).…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…Germination evaluation of intergeneric hybrids between Citrus and Poncirus indicated that coated seeds led to a longer germination period and seed coat removal did not influence germination rate [6]. However, in our work, 60 days after sowing, plant emergence was higher for Rangpur lime coated seeds (75%) than for Rangpur lime decoated seeds (15%) (figure 2).…”
Section: Resultscontrasting
confidence: 55%
“…Usual germination rates for fresh citrus seeds are higher than 85% [5]. Temperatures between (30 and 35)°C lead to maximum seed germination, although it may occur at temperatures as low as 15°C [5,6].…”
Section: Introductionmentioning
confidence: 99%